(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The data spans an extended period from 2009 to 2016, covering the 24th solar cycle. The EOF model decomposes the TEC data into base functions and corresponding coefficients, effectively capturing the influence of solar and geomagnetic activity on TEC variations.The first three EOF modes account for approximately 98% of the total variance in the observed data, indicating their significance in representing the temporal and spatial characteristics of the ionosphere. To characterize the solar-cycle, annual, and semi-annual dependencies, the Fourier Series Analysis (FSA) is applied to modulate the first three EOF coefficients with solar (F10.7) and geomagnetic (Ap and Dst) indices. The TEC model is validated under various solar and geomagnetic conditions, including daytime and nighttime periods. The study finds a positive correlation (0.85) between averaged daily GPS-TEC and averaged daily F10.7, indicating the ionosphere’s time-varying characteristics dependent on solar activity. The EOF model’s validity and reliability are assessed by comparing it with GPS-TEC data and standard global ionospheric models (IRI2016 and SPIM). The performance of the standard ionospheric models is relatively better during High Solar Activity (HSA) periods compared to Low Solar Activity (LSA) periods. The paper showcases the utility of the EOF model in understanding and characterizing ionospheric behavior under different solar and geomagnetic conditions.